Political Expressionism of Women Politicians Amidst the Discourse of the Patriarchal Paradox - Yeby Ma'asan Mayrudin; M. Dian Hikmawan; Moh. Rizky Godjali; Herlina (UIN Sunan Gunung Djati, 2026)
The barriers in expressing political missions for women politicians are due to the dominance of patriarchal structures. This article aims to discuss the dialectic of political expressionism of Banten women politicians amidst the paradox of patriarchy in the organization of political parties and their existence in parliament. Political expressionism is a perspective that attempts to describe the expression of political attitudes and ideas that tend to be emotional and reflective. Therefore, the political expressionism of women politicians is an expression of sentimental political attitudes and ideas of women politicians due to the mental pressure of double burdens, gender discrimination and symbolic violence. A qualitative approach with a transcendental phenomenological is used to explain the